The Influence of Market Prices, Income, and Tastes on Demand for Fashion Products in the Virtual Market on the Shopee Application - Juliani Pudjowati; Susi Tri Wahyuni; Siti Nurul Asyiyah; Mas’adah Mas’adah (Jurnal Mantik, 2023)
This study aims to find out "The Influence of Market Prices, Income, and Tastes both partially and simultaneously on the Demand for Fashion Products in The Virtual Market on Shopee Applications". The sample of this study is a Student of Development Economics of Bhayangkara University Surabaya. Sampling techniques are performed using saturated sampling techniques. This data test uses normalias test, reliability test, and validity test, multiple linear regression test, F Test, T Test, R Square Test, and Dominant Test. The results of this study show that variable market prices, income, and tastes positively and significantly affect the demand for fashion products. Among the variables of market prices, income, and tastes, the dominant variable towards the demand for fashion products in the virtual market on the Shopee App is the variable tastes.